SCIENCE PROCESS SKILLS ANALYSIS OF STUDENTS IN BASIC ELECTRONICS PRACTICE - Ikbal, Muh. Syihab; Hasanah, Andi Uswatun (UIN Sunan Gunung Djati Bandung, 2022)
This research is a quantitative descriptive study that aims to analyze students' science process skills in introductory electronics practicum. This research was conducted in the basic electronics laboratory, Physics Education Study Program, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. The research subjects are physics education students batch 2020 who program Basic Electronics courses in the third semester, the 2021/2022 academic year. The research subjects were 60 students spread evenly in 3 classes: Physics A, Physics B and C. The instrument used was an observation sheet. The results of this study indicate that students of the Physics Education study program class of 2020, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar, who programmed the Basic Electronics course in the odd semester of the 2021/2022 academic year, have good science process skills in introductory electronics practicum.